VD_FINDINFO HC / 2010 / 367 vom 13. Juli 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, POUVOIR D'EXAMEN LIMITÉ, SUBSTITUTION DE PARTIE, BAIL À LOYER | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 261 al. 1 CO, 457 al. 1 CPC, 457 CPC, 64 al. 2 CPC, 9 Cst., 23 al. 2 LPEBL, 23 LPEBL